2022
DOI: 10.7759/cureus.32981
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Increased Oxidative Stress and Tumor Biomarkers Related to Polyaromatic Hydrocarbons Exposure for Different Occupational Workers in Makkah, Saudi Arabia

Abstract: Introduction: Exposure to occupational polyaromatic hydrocarbons (PAHs) is correlated with several adverse effects on human health, including bladder, lung, and skin cancer. The correlation between PAH exposure and oxidative stress and tumor markers needs to be further explored. Therefore, we conducted this study to examine the effect of acute exposure to PAHs on oxidative stress and tumor marker levels in occupational workers during the Hajj season in Makkah. Methods: We conducted a cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…8-Hydroxy-2-deoxyguanosine (8-OH-dG) is generated following the repair of DNA damage which is caused by reactive oxygen species (ROS); thus, it is considered as one of the most widely known markers of DNA oxidative damage. 22 Previous works have shown that DNA damage and oxidative stress caused by different factors 23 are significantly associated with the atherosclerosis and heart failure, 24 and the role of this oxidative damage in the onset and contribution to progression of this pathologic condition need to be more clarified. On the other hand, previous studies demonstrate an association between increased levels of 8-OH-dG and hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…8-Hydroxy-2-deoxyguanosine (8-OH-dG) is generated following the repair of DNA damage which is caused by reactive oxygen species (ROS); thus, it is considered as one of the most widely known markers of DNA oxidative damage. 22 Previous works have shown that DNA damage and oxidative stress caused by different factors 23 are significantly associated with the atherosclerosis and heart failure, 24 and the role of this oxidative damage in the onset and contribution to progression of this pathologic condition need to be more clarified. On the other hand, previous studies demonstrate an association between increased levels of 8-OH-dG and hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of oxidative stress and tumor markers have been reported in occupationally PAH-exposed populations (8). An increased risk of stomach or gastrointestinal cancer has also been reported in the general population in association with smoked or grilled foods, such as fish and meat products, that become contaminated with PAHs during preparation (4,5,9).…”
Section: Introductionmentioning
confidence: 98%